(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Peptic ulcer is diagnosed at endoscopy where there is a mucosal break of 5mm or larger covered with fibrin. Mucosal breaks smaller than 5 mm are called erosions that do not penetrate the muscularis mucosa whereas an ulcer extends through the muscularis mucosa in the sub-mucosa. Objective:To determine the clinical picture, epidemiological aspectof peptic ulcer in children from birth to sixteen years of age and determine the relationship of the clinico-epidemiological aspect of the disease and the socio-demographic features. Methods: Fifty-three patients with an age ranged from birth to 16 years presented with gastrointestinal tract complaint and diagnosed to have peptic ulcer by endoscopic findings. The data was collected by viewing the case sheet of every child included in the study using special questionnaire to obtain socio-demographic information. Results:The mean age was (10.73±5.2) and the majority of the patients (54.72%) were in the age range (11-16) years old, with a male to female ratio of 2.5:1. Duodenal ulcer (66.04%) is more common than gastric ulcer (33.96%). There is significant association between age groups and type of peptic ulcer. Negative family history was found in (71.7%) of patients. Hematemesis is the most common clinical feature present in (69.81%). Conclusions:It is important to investigate children with recurrent abdominal pain, nocturnal pain and positive family history of the disease. Further studies for longer duration are required to follow up complications and healing or chronicity to the adult life. Key words:Peptic ulcer, children, clinico-epidemiological view.